Resonance Raman study of the superoxide reductase from Archaeoglobus fulgidus, E12 mutants and a 'natural variant' - Todorovic, Smilja (2009)
The resonance Raman (RR) spectra of the oxidized wild-type Archaeoglobus fuglidus 1Fe-Superoxide reductase (SOR), E12V and E12Q mutants were studied at different pH conditions upon excitation in resonance with the pH-dependent charge transfer transition to the ferric iron. The wild-type SOR from Nanoarchaeum equitans that lacks the highly conserved glutamate residue was investigated as a ′natural variant′. No substantial differences were observed in the RR spectra of the active sites of the A. fulgidus proteins. Based on the component analysis in the metal-ligand stretching region the modes involving the Fe-S(Cys) stretching coordinates have been identified. The frequencies of these modes reflect the electronic properties of the Fe-S bond which are related to the catalytic activity of SORs, including reduction of superoxide and product dissociation. Moreover, hydroxide binding to the E12 mutant proteins was demonstrated at high pH. It was further observed that the ferric active site of all three SORs from A. fulgidus senses the presence of phosphate, which possibly replaces the hydroxide at high pH.